NEURAL CORRELATES OF ASSOCIATIVE AND ITEM RECOGNITION IN AGING. (16th November 2018) - Patterson, M; Leaver, E; Nibblett, K; Rubenstein, S; Kline, S
Abstract: Thirty younger and 17 older adults were taught the strategy of interactive imagery for learning word pairs. After studying pairs, participants completed associative and item recognition tests. Older adults' responses were slower than younger adults' and associative recognition responses were slower than item recognition. However, for accuracy, there were no differences between age group or test type (item vs. associative), contrary to the expectations of the associate deficit hypothesis. Analysis of the EEG recordings indicated that, at parietal electrode sites, peak amplitudes were significantly larger in response to the associative recognition test compared to the item recognition test. Additionally, a significant 3-way interaction was observed at electrode Cz. The item recognition task elicited larger peak amplitudes to new test items compared to old test items in both age groups. Interestingly, while the associate recognition test also elicited larger peak amplitudes to new and rearranged test pairs as compared to old test pairs in younger adults, this difference did not exist for older adults. Implications for memory training of older adults will be discussed.